2018
DOI: 10.1123/pes.2017-0163
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Changes in Sedentary Time, Physical Activity, and Body Mass Index in Young Schoolchildren: A 3-Year Longitudinal Study

Abstract: Time spent in ST increases due to displacement of time in LPA. This reinforces public health measures and suggests the need for interventions focusing on offsetting the decline ST and increasing MVPA during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Based on the review inclusion criteria and data availability, 521 studies were further excluded. Thus, 52 studies met the inclusion criteria and were included in the quantitative analysis representing a total sample of 22,091 children and adolescents (Figure ; PRISMA flow diagram). A subset of 31 studies with exactly 1 year of follow‐up data were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review inclusion criteria and data availability, 521 studies were further excluded. Thus, 52 studies met the inclusion criteria and were included in the quantitative analysis representing a total sample of 22,091 children and adolescents (Figure ; PRISMA flow diagram). A subset of 31 studies with exactly 1 year of follow‐up data were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the AVG group showed an increasing trend in MPA and VPA. The importance of this significant increase in LPA lies in the opportunity to replace sedentary time with LPA [ 69 ], and in this way, to fight against the opposite trend of replacing LPA with more sedentary time that occurs in pre-adolescence and adolescence [ 70 ]. In addition, LPA has a strong influence on cardio-metabolic health [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, girls spent an average of almost 6 h per day in SB; this was compared to 5½ h spent by boys. Previous studies have reported that spending more time in SB is associated with unfavourable BC indicators in children [ 53 , 54 ]. Furthermore, it has been reported that MVPA levels did not influence the relationship between SB and adiposity in children [ 53 ].…”
Section: Discussionmentioning
confidence: 99%